2012
DOI: 10.1016/j.cplett.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and magnetic properties of Ni-doped ZnO micro-rods grown by the spray pyrolysis method

Abstract: Undoped and Ni-doped ZnO micro-rod arrays were successfully synthesized by the spray pyrolysis method on glass substrates. Analysis of the samples with x-ray diffraction and scanning electron microscopy showed that these micro-rod arrays had a polycrystalline wurtzite structure with a highly c-axis preferred orientation. Photoluminescence studies at both 300 K and 10 K show that the incorporation of nickel leads to a relative increase in the visible blue light band intensity. Magnetic measurements indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 49 publications
(43 reference statements)
2
22
0
1
Order By: Relevance
“…The intensity of the peak (626 nm) due to oxygen defects decreases with increasing Ni doping concentration which shows there may be some recombination occur [41]. Fig.…”
Section: (V O ) Zinc Vacancies (V Zn ) Oxygen Interstitial (O I ) mentioning
confidence: 93%
See 1 more Smart Citation
“…The intensity of the peak (626 nm) due to oxygen defects decreases with increasing Ni doping concentration which shows there may be some recombination occur [41]. Fig.…”
Section: (V O ) Zinc Vacancies (V Zn ) Oxygen Interstitial (O I ) mentioning
confidence: 93%
“…[35,41]. Liu et al reported that NiO is an antiferromagnetic material with Neel temperature of 520K, while at room temperature it is super paramagnetic [44].…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…Further observations reveal that all the peaks gradually diminish with the increase in Ni concentration due to quenching effect [64][65][66], with the pristine ZnO sample showing the most intense bands. Yilmaz et al also observed similar decrease in the intensity of the emission peaks with the increase in Ni content in rod-shaped particles of Ni-doped ZnO synthesized by spray pyrolysis [67]. The increase in Ni concentration leads to increase in the impurities at Zn sites.…”
Section: Optical Properties Of the Ni-doped Zno Nanoplateletsmentioning
confidence: 80%
“…However, in many reports the as observed magnetic moment value is comparatively low (of the order of micro to mili emu/g) even for higher percentage of TM doping [11,12,23]. Also the FM to PM transition temperature (T C ) is not high in many cases [21,22]. In this scenario, synthesis of TM doped ZnO nanoparticles showing FM above room temperature with a high moment, high crystallinity and high T C still remains a significant challenge for future spintronic devices.…”
Section: Introductionmentioning
confidence: 95%
“…Many researchers have tried to synthesize ZnO based DMS nanostructure [16,21,22]. However, in many reports the as observed magnetic moment value is comparatively low (of the order of micro to mili emu/g) even for higher percentage of TM doping [11,12,23].…”
Section: Introductionmentioning
confidence: 99%